2016
DOI: 10.1093/pasj/psw064
|View full text |Cite
|
Sign up to set email alerts
|

Survey of period variations of superhumps in SU UMa-type dwarf novae. VIII. The eighth year (2015–2016)

Abstract: Continuing the project described by Kato et al. (2009), we collected times of superhump maxima for 128 SU UMa-type dwarf novae observed mainly during the 2015-2016 season and characterized these objects. The data have improved the distribution of orbital periods, the relation between the orbital period and the variation of superhumps, the relation between period variations and the rebrightening type in WZ Sge-type objects. Coupled with new measurements of mass ratios using growing stages of superhumps, we now … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 156 publications
0
21
0
Order By: Relevance
“…While this is roughly in agreement with the accretion rates estimated from observations (Townsley & Gänsicke 2009;Pala et al 2017), the theoretical framework outlined above fails to re-produce a number of observational properties of the Galactic population of CVs: (i) the predicted fractions of CVs above and below the period gap ( 1 per cent and 99 per cent, respectively, de Kool 1992; Kolb 1993;Howell et al 2001) are in clear disagreement with the observations (e.g. 23 per cent and 77 per cent, Gänsicke et al 2009, though the observed samples are typically magnitude-limited, and hence biased towards more luminous CVs); (ii) period bouncers are expected to be the main component ( 40 − 70 per cent) of the present-day Galactic CV population but only a small number of such systems has been identified (Patterson et al 2005;Unda-Sanzana et al 2008;Littlefair et al 2006;Patterson 2011;Kato et al 2015Kato et al , 2016McAllister et al 2017;Neustroev et al 2017;Pala et al 2018); (iii) there are clues of the presence of additional AML mechanisms that are not accounted for by the standard model of CV evolution (Patterson 1998; Knigge et al 2011;Schreiber et al 2016;Pala et al 2017;Zorotovic & Schreiber 2017;Belloni et al 2018;Liu & Li 2019), although the physical origin of this enhanced AML is still unclear.…”
mentioning
confidence: 88%
“…While this is roughly in agreement with the accretion rates estimated from observations (Townsley & Gänsicke 2009;Pala et al 2017), the theoretical framework outlined above fails to re-produce a number of observational properties of the Galactic population of CVs: (i) the predicted fractions of CVs above and below the period gap ( 1 per cent and 99 per cent, respectively, de Kool 1992; Kolb 1993;Howell et al 2001) are in clear disagreement with the observations (e.g. 23 per cent and 77 per cent, Gänsicke et al 2009, though the observed samples are typically magnitude-limited, and hence biased towards more luminous CVs); (ii) period bouncers are expected to be the main component ( 40 − 70 per cent) of the present-day Galactic CV population but only a small number of such systems has been identified (Patterson et al 2005;Unda-Sanzana et al 2008;Littlefair et al 2006;Patterson 2011;Kato et al 2015Kato et al , 2016McAllister et al 2017;Neustroev et al 2017;Pala et al 2018); (iii) there are clues of the presence of additional AML mechanisms that are not accounted for by the standard model of CV evolution (Patterson 1998; Knigge et al 2011;Schreiber et al 2016;Pala et al 2017;Zorotovic & Schreiber 2017;Belloni et al 2018;Liu & Li 2019), although the physical origin of this enhanced AML is still unclear.…”
mentioning
confidence: 88%
“…Given our updating of the superhump-mass ratio relations above, we revisit the analysis of donor star properties in Knigge (2006) and Knigge et al (2011). Firstly, P sh values for all SU UMa-type DNe in the Patterson et al (2005) sample (70 systems) were replaced by P B sh measurements from the SU UMa-type DNe survey of Kato et al (2009Kato et al ( , 2010Kato et al ( , 2012Kato et al ( , 2013Kato et al ( , 2014aKato et al ( ,b, 2015Kato et al ( , 2016Kato et al ( , 2017. For a number of systems, P orb was also updated, either from measurements made by Tables 2 and B1 Patterson et al (2005).…”
Section: Donor Masses and Radii Of Superhumping Cvsmentioning
confidence: 99%
“…Kato et al (2016) reported a superhump period of 0.056219 d. Using the two longest runs (as these were the cleanest with multiple orbital cycles) presented in this paper (S8649 and S8651), a superhump pe- riod of 0.0562(±1) d was found. This period agrees with the superhump period found by Kato et al (2016). Our average light curve of run S8653, folded on the ephemeris HJD max = 2457145.22513(±1) + 0.0562(±1) E, is shown in Figure 9.…”
Section: Asassn-15hmmentioning
confidence: 57%
“…Highlights from the survey include the discovery of a fair number of new AM CVn systems including the 10-min binary ES Ceti , and new insights in the nature of dwarf nova oscillations and quasi-periodic oscillations in CVs (Warner 2004). ; d : period determined by Kato et al (2016); r: r magnitude of the system in quiescence. This magnitude is an estimate and is accurate to 0.1 mag.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation